2017
DOI: 10.3390/rs9050398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple Linear Regression, Cubist Regression, and Random Forest Algorithms to Estimate Daily Air Surface Temperature from Dynamic Combinations of MODIS LST Data

Abstract: Abstract:Recently, several methods have been introduced and applied to estimate daily air surface temperature (T a ) using MODIS land surface temperature data (MODIS LST). Among these methods, the most common used method is statistical modeling, and the most applied algorithms are linear/multiple linear regression models (LM). There are only a handful of studies using machine learning algorithm models such as random forest (RF) or cubist regression (CB). In particular, there is no study comparing different com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 44 publications
2
76
0
1
Order By: Relevance
“…This randomness and requiring no assumption of the probability distribution in predictive variables, increase model prediction accuracy and robustness against over-fitting [80,81]. Finally, an optimal prediction model is generated by aggregating all the "trees" that form the "forest" [82,83].…”
Section: Comparison To Other Modeling Methodsmentioning
confidence: 99%
“…This randomness and requiring no assumption of the probability distribution in predictive variables, increase model prediction accuracy and robustness against over-fitting [80,81]. Finally, an optimal prediction model is generated by aggregating all the "trees" that form the "forest" [82,83].…”
Section: Comparison To Other Modeling Methodsmentioning
confidence: 99%
“…Since available, MODIS LST data has been used for various studies, such as evaluating and monitoring urban heat islands [11][12][13][14][15], estimating air surface temperatures (Ta) [16][17][18][19], retrieving soil moisture [20,21], drought assessment [22], and hydrology applications [23]. Most of these studies have shown that the changes of land surface properties (e.g., normalized difference vegetation index (NDVI), elevation, and land use/cover types) will result in the variations of LST [3].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies used point data from weather stations located 1.5 m to 2.0 m above the land surface [33][34][35]. LST and Ta are not equivalent, and their relationship is multifaceted due to the complex surface energy budget and the multiple related variables between them [17][18][19]36]. Therefore, the relationship between Ta and elevation is different from those of LST and elevation.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that CB was the best choice for predicting urban impervious surface cover. Noi et al (2017) compared the results of Multiple Linear Regression, Cubist Regression, and Random Forest Algorithms in estimation of daily air surface temperature. They concluded that using different combinations of data, RF or CB algorithms resulted in high accuracies.…”
Section: Introductionmentioning
confidence: 99%